(untitled) (Anclajes, 2011)
Th e Article proposes the problem of the inadequacy of the work El matadero , by Esteban Echeverría, in its context of production, which made it remain inedited for over thirty years. On the one hand, the scripts that shape the cultural policies of the Generación del 37, and on the other hand the present hypothesis about the place of El matadero in that context, are regarded in that direction. Not only does such looking through contribute to propose new approaches to the beginnings of literature and literary criticism in Argentina, but attempts a refl ection on the general problem of the cultural and literary boundaries. This text tries, fi nally, to put under suspicion the construction of an homogeneous cultural identity, in a germinal map of Argentine Literature which focuses on the Río de la Plata and whose boundaries haven ́t been very questioned since the creation of that map to the present. The question about the thirty-year margined literary work intends to be the question about the strategies, exigences and reticences in the projection of a preferable and defi nite literature and culture.